The Effect Of Using Narrative Poster Learning Media On Historical Literacy Of Science Subjects Of Grade VI Elementary School Students - Salsabila Maharani Aura Salim; Angga Setiawan; Indah Yunitasari (Universitas Islam Balitar, 2025)
Historical literacy is the ability to understand, analyze, and connect past eventswith the present context. Based on PISA 2018 data, Indonesian students' readingliteracy scores are still below the international average, reflecting the low abilityto understand texts, including historical texts. The results of initial observations atSDN 1 Mlinjon, SDN 2 Mlinjon, and SDN 2 Suruh showed that the historicalliteracy of grade VI students was still relatively low. This study aims to determinethe effect of the use of narrative poster learning media on historical literacy in thescience subject of grade VI Elementary School students. This study uses aquantitative approach with a quasi-experimental design of the non-equivalentcontrol group design type. The subjects of the study consisted of 31 students fromthe experimental class (SDN 1 and SDN 2 Mlinjon) and 23 students from thecontrol class (SDN 2 Suruh), who were selected using a purposive samplingtechnique. Data collection was conducted through tests and interviews, while dataanalysis used independent sample t-test with the help of SPSS 25. The results ofthe analysis showed a significance value of 0.000 (<0.05), which means that thereis a significant influence of the use of narrative poster media on improvingstudents' historical literacy. Thus, narrative poster media can be an alternativeeffective learning media in improving the historical literacy of elementary schoolstudents. This study can also be a reference for the development of othernarrative-based learning media.